Analisa Penerapan SMK 3 Fasyankes Mengacu Kepmenkes No. 52 Tahun 2018 di Puskesmas Medan Deli dimasa Pandemi Covid-19 - Dewi Marina Katalena Sidabutar; Bernard Hasibuan; Soehatman Ramli (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2022)
Covid-19 has been declared a global pandemic by WHO. The impact of this large-scale national restriction occurs in all aspects of life, be it the economy, business, work, worship, education, public services, health facilities, and others. Management of health facilities (hospitals, health centers) must make maximum efforts to minimize and control hazards and risks; prevention of accidents and injuries; also maintain safe conditions. The purpose of this study is to analyze the implementation of SMK3 Fasyankes referring to Kepmenkes No. 52 of 2018 at the Medan Covid-19 Health Center during the pandemic. The type of research used in this study is a qualitative research with a descriptive approach. Based on the data collection method, this research uses field research methods. The results of the study explained that the analysis of the implementation of SMK3 at the Medan Deli Health Center during the Covid-19 pandemic was not good enough. The recording and reporting of the implementation of SMK3 at the Medan Deli Health Center during the Covid-19 pandemic had an index of 0.58 or 58%, "This means that the implementation of SMK3 Fasyankes has not been optimal and the programs that were run during the Covid-19 pandemic followed directions from the central government, the K3 The health center has not set a special program related to the Covid-19 disaster management. Researchers suggest to the management to discuss K3 properly and continuouslyKeywords: Health Facilities, Kepmenkes No. 52, Covid-19